Hubungan antara Kepercayaan dengan Komitmen Organisasi di Sekolah Menengah Atas Negeri Wilayah 1 Kota Administrasi Jakarta Timur - Istiasmidiati Wardiningrum; Neti Karnati; Diah Armeliza (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2016)
This study aims to determine the relationship between trust and organizational commitment of Senior High School in East Jakarta Administration City Region 1. The method used is survey method with the correlational studies and quantitative approaches. Samples were as many as 91 teachers. Sampling using simple random sampling by the formula Slovin and data collection using questionnaires. From the results of hypothesis testing, obtained t count equal to 22.62, which means bigger than t table 1.99. Thus, the alternative hypothesis (Ha) are accepted positively. Of the coefficient of determination, confidence contributed 85.19% to organizational commitment of Senior High School in East Jakarta Administration City Region 1. Then, based on the results of the research, it is known that the higher the confidence, the higher the level of organizational commitment of Senior High School in East Jakarta Administration City Region 1.